Strategies adopted by local banks to attract new customers and retain existing customers : a case study on Handelsbanken in Luleå - Hadi Jama, Mona (2010)
Handelsbanken (HB) is one of the four largest banks in the Nordic countries and branch office operations are organized into eleven regional banks, six in Sweden one each in Norway, Finland, Denmark and two in Britain. HB is known to have a strong position in the Swedish market. A study was conducted to investigate how the local branch of HB in Luleå, market itself to meet banking needs of the young people between 13-18 years and how did they try to affect the decisions to retain their existing bank by not switching to another bank. The methodology adopted in this research started with preparation of a set of questionnaire followed by a verbal interview of a bank manager and later on all the answers received were compiled up for analysis and to draw conclusions from them. The research analysis has shown that HB does not segment their customers and do not possess any aim for their marketing. It does not have any specific marketing strategy for the younger customers in the age of 13-18. HB deals equally with all customers by fulfilling all their needs and maintaining long-term relationship. HB also believes their satisfied customers are their marketers, and they turn out to attract new customers. HB also uses their existing customers to get hold of their children’s to convince them to be their customer. HB believes its strong brand name and its position in the market, helps them when attempting to attract new customers. HB also thinks their web page is well defined to attract new customers as it has provided all the necessary information’s required to attract new customers as well as protect existing customers from switching over to other banks. HB emphasizes more on the quality control and development of the banking services to maintain long term relationship with their existing customers, who are in fact their real time marketers. HB also organizes regular training programs to update the knowledge of their banking services, to enhance their customer services and maintain a higher satisfaction level of the ...